Numerical experimental evaluation of the aerodynamic drag of the air curtain in Vertical Open Refrigerated Display Cabinets - Nascimento, Samuel Mariano do (2019)
This paper presents the experimental and numerical results of a set of air curtain evaluations in a Vertical Open Refrigerated Display Cases (VORDC) when subjected to external disturbances due to the transfer of people in front of the air curtain. Previous experimental studies identified that the stability of the air curtain depends on the climatic conditions and ambient air movement inside the stores. The ambient air and VORDC air curtain can be disturbed during the movement of people in front of the VORDC, causing a certain amount of cold air to flow out of the VORDC and consequently hot and humid air entering. It is not possible to quantify exclusively the increase in energy consumption due to the transfer of people in the real case, due to the other variables involved in the process. Thus, a robot (Automated Mannequin for Interference Reproduction in the Air Curtain - MARIA) was mounted on a rail placed around the VORDC, in a climate chamber with controlled environment according to climatic class (n. º 3: T=25°C; =60%). MARIA performed clockwise and counterclockwise movements around the VORDC, with velocities of 0.2 m.s-1 at 0.8 m.s-1, with a pitch of 0.2 m.s-1. For the numerical evaluation, a 3D CFD model was developed to predict and analyze the air flow and heat transfer in the air curtain and outside both ways, refrigerated space and ambient air due to transfer of a body parallel to the air curtain.